Differential diagnosis of progressive intellectual and neurological deterioration in children. (24th September 2020) - Verity, Christopher; Baker, Elaine; Maunder, Polly; Pal, Suvankar; Winstone, Anne Marie
Abstract : Aim: To report the differential diagnosis in children with progressive intellectual and neurological deterioration (PIND) in the UK. Method: Since 1997 the PIND Study has searched for variant Creutzfeldt‐Jakob disease (vCJD) in children, using the British Paediatric Surveillance Unit to perform prospective surveillance of those younger than 16 years with PIND. Results: From May 1997 to October 2019, 2255 children meeting PIND criteria had been notified, of whom 2008 (1085 males, 923 females) had underlying diagnoses. There were over 220 different diseases, including six cases of vCJD. The numbers presenting in four age groups were: <1 year, 805 (40%); 1 to 4 years inclusive, 825 (41%); 5 to 9 years inclusive, 264 (13%); and 10 to 15 years inclusive, 114 (6%). The two largest ethnic groups were White and Pakistani (58.2% and 17% of diagnosed cases). The most common diseases in these two ethnic groups are shown for the four age groups. The distribution of diseases varied with age but was quite similar in White and Pakistani children. Interpretation: This paper provides a unique guide to the complex differential diagnosis of childhood PIND, showing considerable differences between four age groups, but similarities between ethnic groups. The PIND Study still provides the only systematic surveillance for vCJD in children in the UK. What this paper adds: The prevalence of diseases causing childhood progressive intellectual and neurological deterioration in the UK is low (approximately 0.1/1000 live births). There were more than 220 different disorders, mainly genetically determined. The majority of disorders presented early in childhood: 81% before the age of 5 years. There were similarities in the disease spectrum in White and Pakistani children. What this paper adds: The prevalence of diseases causing childhood progressive intellectual and neurological deterioration in the UK is low (approximately 0.1/1000 live births). There were more than 220 different disorders, mainly genetically determined. The majority of disorders presented early in childhood: 81% before the age of 5 years. There were similarities in the disease spectrum in White and Pakistani children. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Video Podcast: https://youtu.be/QbUG-ZVJLHc This article is commented on by van Karnebeek on page 243 of this issue. Diagnóstico diferencial del deterioro intelectual y neurológico progresivo en niños: Objetivo: Informar el diagnóstico diferencial en niños con deterioro intelectual y neurológico progresivo (PIND) en el Reino Unido. Método: Desde 1997, el estudio PIND ha buscado una variante de la enfermedad de Creutzfeldt‐Jakob (vCJD) en niños, utilizando la Unidad Británica de Vigilancia Pediátrica para realizar una vigilancia prospectiva de los menores de 16 años con PIND. Resultados: Desde Mayo de 1997 hasta Octubre de 2019, se notificaron 2255 niños que cumplían con los criterios de PIND, de los cuales 2008 (1085 varones, 923 mujeres) tenían diagnósticos subyacentes. Había más de 220 enfermedades diferentes, incluidos seis casos de vCJD. Los números que se presentaron en cuatro grupos de edad fueron: menos de 1 año, 805 (40%); 1 a 4 años inclusive, 825 (41%); 5 a 9 años inclusive, 264 (13%); y de 10 a 15 años inclusive, 114 (6%). Los dos grupos étnicos más grandes eran blancos y paquistaníes (58, 2% y 17% de los casos diagnosticados). Las enfermedades más comunes en estos dos grupos étnicos se muestran para los cuatro grupos de edad. La distribución de las enfermedades varió con la edad, pero fue bastante similar en los niños blancos y paquistaníes. Interpretación: Este artículo proporciona una guía única para el diagnóstico diferencial complejo de la PIND en la niñez, mostrando diferencias considerables entre cuatro grupos de edad, pero similitudes entre grupos étnicos. El estudio PIND todavía proporciona la única vigilancia sistemática de vCJD en niños del Reino Unido. Diagnóstico diferencial de deterioração intelectual e neurológica progressiva em crianças: Objetivo: Relatar o diagnóstico diferencial em crianças com deterioração intelectual e neurológica progressiva (DNIP) no Reino Unido. Método: Deste 1997 o estudo DNIP tem pesquisado a variante da doença de Creutzfeldt‐Jakob (vDCJ) em crianças, usando o Levantamento Pediátrico Britânico para fazer um acompanhamento prospective daqueles com DNIP e menor de 16 anos. Resultados: De maio de 1997 a outubro de 2019, 2.255 crianças que atendiam aos critérios para DNIP foram notificadas, das quais 2008 (1085 do sexo masculino, 923 do sexo feminino) tinham diagnósticos de base. Houve mais de 220 doenças diferentes, incluindo seis casos de vDCJ. Os números apresentados em quatro grupos etários foram: menos de 1 ano, 805 (40%); 1 a 4 anos inclusive, 825 (41%); 5 a 9 anos inclusive, 264 (13%); e 10 a 15 anos inclusive, 114 (6%). Os dois maiores grupos étnicos foram branco e paquistanês (58, 2% e 17% dos casos diagnosticados). As doenças mais comuns nestes dois grupos étnicos são mostradas para os quatro grupos etários. A distribuição das doenças various com a idade, mas foi bem similar em crianças brancas e paquistanesas. Interpretação: Este artigo fornece um guia único para o complexo diagnóstico diferencial de DNIP na infância, mostrando diferenças consideráveis entre quatro grupos etários, mas similaridades entre grupos étnicos. O estudo DNIP ainda fornece o único levantamento sistemático de vDCJ em crianças do Reino Unido.